2018
DOI: 10.1007/s00484-018-1543-1
|View full text |Cite|
|
Sign up to set email alerts
|

Association between cancer risk and polycyclic aromatic hydrocarbons’ exposure in the ambient air of Ahvaz, southwest of Iran

Abstract: Nowadays, a large number of health endpoints such as disease rates, treatment costs, and death, by air pollutants, have been a serious health problem for humans. One of the most hazardous air pollutants, which is highly dangerous for human health, is polycyclic aromatic hydrocarbons (PAHs). The existence of the emission of industries' pollutants and seasonal variations are the primary agents affecting PAHs' concentration. The purposes of this study were to calculate the cancer risk and measure PAHs' exposure i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…In the world (United States, Europe, and Asia), several studies have reported the effects of air pollution on human health. The results of these studies showed that higher concentrations of PM 10 , O 3 , NO 2 , SO 2 , metals, and polyaromatic hydrocarbons (PAHs) can increase the risk of morbidity and mortality due to respi-ratory infections, chronic obstructive pulmonary disease, asthma attacks, coughing, reduced lung function, eye irritation, cardiovascular disease, stroke, respiratory and cardiovascular death) (14)(15)(16)(17)(18)(19)(20).…”
Section: Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…In the world (United States, Europe, and Asia), several studies have reported the effects of air pollution on human health. The results of these studies showed that higher concentrations of PM 10 , O 3 , NO 2 , SO 2 , metals, and polyaromatic hydrocarbons (PAHs) can increase the risk of morbidity and mortality due to respi-ratory infections, chronic obstructive pulmonary disease, asthma attacks, coughing, reduced lung function, eye irritation, cardiovascular disease, stroke, respiratory and cardiovascular death) (14)(15)(16)(17)(18)(19)(20).…”
Section: Contextmentioning
confidence: 99%
“…There are reports on the considerable toxicity of airborne metals to the lung (39). Polycyclic Aromatic Hydrocarbons (PAHs) are a group of hydrocarbons that are composed of multiple aromatic rings (16). Human exposure to PAHs can cause different health effects (15,16).…”
Section: Major Airborne Pollutants Harmful To the Lungmentioning
confidence: 99%
“…Among POPs, PAHs are lipophilic and can easily infiltrate skin cells, binding to DNA and causing its damage [19]. Hence, these air pollutants are recognized as mutagens and/or carcinogens [124,127]. Airborne metals are not biodegradable; they remain in cells for a long time and act as genotoxic agents, impairing the skin DNA repair capacity [128].…”
Section: Skin Cancermentioning
confidence: 99%
“…1 Cancer by the new cases of 14 million and the annual mortality of 8.2 million is the second leading cause for mortality after cardiovascular diseases in the world. [2][3][4][5][6] Lung cancer is the most fatal and expensive cancer worldwide. 7 Among the various cancers, lung is only the cancer which has different incidences in Iran and world 8 and undoubtedly its incidence in Iran has had an underestimation.…”
Section: Introductionmentioning
confidence: 99%